2015
DOI: 10.1186/s12950-015-0079-y
|View full text |Cite
|
Sign up to set email alerts
|

Mucus mediated protection against acute colitis in adiponectin deficient mice

Abstract: BackgroundAcute ulcerative colitis is an inflammation-driven condition of the bowel. It hampers the general homeostasis of gut, resulting in decreased mucus production and epithelial cell renewal. Adiponectin (APN), an adipocytokine, is secreted by the adipose tissue and has been debated both as a pro-inflammatory or anti-inflammatory protein depending on the disease condition and microenvironment. The present study delineates the role of APN depletion in mucus modulation in a model of acute colitis.MethodsAPN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…Depletion of bacterial communities reduced goblet counts that could be attributed to either regulation of goblet cell apoptosis or goblet cell development or both. Goblet cells are integral to the maintenance of the mucus layer, which in turn, regulates the composition of the gut microflora (findings from previous studies [64]). As mucus layer offer protection against inflammation and tumor progression [44], factors that disrupts this protection cycle will lead to gut inflammation and carcinogenesis.…”
Section: Discussionmentioning
confidence: 89%
“…Depletion of bacterial communities reduced goblet counts that could be attributed to either regulation of goblet cell apoptosis or goblet cell development or both. Goblet cells are integral to the maintenance of the mucus layer, which in turn, regulates the composition of the gut microflora (findings from previous studies [64]). As mucus layer offer protection against inflammation and tumor progression [44], factors that disrupts this protection cycle will lead to gut inflammation and carcinogenesis.…”
Section: Discussionmentioning
confidence: 89%
“…Likewise, in another independent study, WT mice treated with DSS and an APN adenovirus were protected (50). In marked contrast, the work of Fayad et al (51,52) reported that DSS treatment and APN absence was protective against colitis, and a reduced inflammatory response was observed. These differences could be explained by variations in methods, the source of KO mice, the form of recombinant APN, and the pathogen status of the animal facilities.…”
Section: Discussionmentioning
confidence: 90%
“…The hypothesis on the protective role of adiponectin in colitis, acting through AdipoR1, is supported by the evidence from Sideri et al [127], who showed that intracolonic AdipoR1 knock down worsened TNBS-induced colitis in mice. In contrast, some studies [211,212] report that APN absence protects against DSS induced colitis. In another study, APN deficiency did not significantly modulate the inflammation in the IL-10 KO model of spontaneous chronic colitis [213].…”
Section: Experimental Studies On Role Of Adipose Tissue In Ibdmentioning
confidence: 86%